TINGKAH LAKU SOSIAL RUSA TIMOR (Cervus timorensis) DI PENANGKARAN BUMI MARINA, MANOKWARI - Madja, Jerianto Tawala; Koibur, Johan F.; Pattiselanno, Freddy (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2018)
Deer is a wild animal that has economi value and can be utilized by the commnity as a source of protein of animal origin so that the deer can be breed by the communty. In papua deer have been cultivated or breed in a relativery large scare. The purpose of cultivation or captivity is to know the daily behavior or deer timor (Cervus timorensis) in brooder breeding condtion with large numbers of pet populations. The time of study for Â±one month is from the beginning of september to the and of september 2017. Using 10 sample from 24 deer in breeding, 3 aduit males, 2 young males, 3 adult females and 1 young females and 1 culf. Using time observation method with observation technique. Analyze data using exel to find the percen tage of social activity from each time period. Each time period was divided into I 06:00-08:00(6,48%); II 08:00-10:00(25,93%); III 10:00-12:00(19,44%); IV 12:00-14:00(7,41%); V 14:00-16:00(6,48) and VI 16:00-18:00(34,26). Our findings showed that social activity/interaction in group much more observed in the afternoon.